Synthes of robust active shielding systems of magnetic field generated by group of high-voltage power lines - Kuznetsov, B.I.; Nikitina, T.B.; Kolomiets, V.V.; Voloshko, A.V.; Vinichenko, E.V.; Bovdui, I.V. (Електротехніка і електромеханіка, 2018)
Aim. The synthesis of robust active shielding system of magnetic field, generated by group of high voltage power lines for
reducing the induction of the initial magnetic field to the sanitary standards level and reducing the sensitivity of the system to
variations in the plant parameters is given. Methodology. The synthesis is based on the solution of a multi-criteria stochastic
game, in which the gain vector is calculated on the basis of the Maxwell equations solutions in the quasi-stationary
approximation. The equilibrium state of the game is based on the stochastic multiagent optimization algorithms of the
multiswarm particles. The initial parameters for the synthesis of active shielding system are the location of the high voltage
power lines with respect to the protected from transmission line space, geometry and number of cables, operating currents, as well
as the size of the protected space and normative value magnetic field induction, which should be achieved as a result of screening.
The objective of the synthesis of the active shielding system is to determine their number, configuration, spatial arrangement,
wiring diagrams and compensation cables currents, setting algorithm of the control systems as well as the resulting value of the
induction magnetic field at the points of the protected space. Results. Robust active shielding system synthesis results for
reduction of a magnetic field generated by group of high voltage power lines is given. The possibility of a significant reduction in
the level of induction of the magnetic field source within and reducing the sensitivity of the system to variations in the plant
parameters is given. Originality. For the first time carried out the synthesis of the robust active shielding systems of magnetic
field generated by group of high voltage power lines within a given region of space. Practical value. Practical recommendations
on reasonable choice of the number and spatial arrangement of compensating cables of robust active shielding systems of the
magnetic field generated by the group of high voltage power lines is given. Цель. Проведен синтез робастной системы активного экранирования магнитного поля, создаваемого группой
высоковольтных линий электропередачи для снижения индукции исходного магнитного поля до уровня санитарных
норм и уменьшения чувствительности системы к изменениям параметров системы. Методология. Синтез основан
на решении многокритериальной стохастической игры, в которой векторный выигрыш вычисляется на основании
решений уравнений Максвелла в квазистационарном приближении. Равновесное состояние игры находится на основе
алгоритмов стохастической мультиагентной оптимизации мультироем частиц. Исходными параметрами для
синтеза системы активного экранирования являются расположение высоковольтных линий электропередачи по
отношению к защищаемому пространству, геометрические размеры, количество проводов и рабочие токи линии
электропередачи, а также размеры защищаемого пространства и нормативное значение индукции магнитного поля,
которое должно быть достигнуто в результате экранирования. Целью синтеза системы активного экранирования
является определение количества, конфигурации, пространственного расположения, схем электропитания и токов
компенсационных кабелей, алгоритма работы системы управления, а также результирующего значения
индукционного магнитного поля в точках защищаемого пространства. Результаты. Приводятся результаты
синтеза робастной системы активного экранирования для уменьшения магнитного поля, создаваемого группой
высоковольтных линий электропередачи. Показана возможность существенного снижения уровня индукции
исходного магнитного поля внутри заданного пространства и снижения чувствительности системы к изменениям
параметров системы. Оригинальность. Впервые проведен синтез робастной системы активного экранирования
магнитного поля, создаваемого группой высоковольтных линий электропередач в данной области пространства.
Практическая ценность. Приводятся практические рекомендации по обоснованному выбору количества и
пространственного расположения компенсирующих обмоток робастных систем активного экранирования
магнитного поля, создаваемого группой высоковольтных линий электропередач